PENGELOLAAN PERILAKU TANTRUM OLEH IBU TERHADAP ANAK USIA 12-48 BULAN - Wenny Ayu Lestari; Christina Erriana Putri; Rini Sugiarti; Fendy Suhariadi (Faculty of Psychology Universitas Islam Sultan Agung Semarang, 2021)
Tantrum is a behavioral disorder experienced by 12-48 - month - child in form of emotional outbursts, for example: destructive behavior or verbally (crying, screaming, whining) over and over again. The reason behind that action is the difficulty of children to understand their feeling and emotion moreover, they have unstable emotions due to discomfort feelings or difficult to deliver what they feel and what they want to their parents or others. This study focused on how mothers manage children's emotions with Tantrum aged 12 - 48 months. Because this research focus on parents with tantrum children, researcher used purposive sampling to specify the subject and collect the data using in-depth interviews. Furthermore, the data was analyzed by Miles and Huberman Model. The result showed that four out of five subjects explicitly reveals that communication and emotional identification were more effective to decrease tantrum behavior gradually. Whereas, one of them use diversion to distract attention. However, it was an ineffective way because, children cannot understand the emotion they feel and how to deliver it in a good way. The result was children will manipulate the surrounding with the same emotion. In this study, the emotion was shown verbally, such as crying loudly and screaming.